A Fine Balance: Developing Clinical Practice Guidelines in Areas Where Evidence is Lacking. Issue 6 (31st July 2015) - Levin, Adeera; Wheeler, David C.
Abstract: Over the last 15 years, numerous clinical practice guidelines have been developed by clinicians driven by national societies and funders of healthcare services. Writing and publication of guidelines have been refined such that a transparent and robust process has evolved. The main purpose of clinical practice guidelines is to provide healthcare professionals with evidence‐based recommendations to assist clinical decision‐making and reduce variability in clinical practice: this benefits patients and the healthcare system. When evidence is abundant and robust, guideline development is relatively straightforward. However, in areas where evidence is lacking, there is a tension between providing advice based on expert opinion while maintaining a clinical equipoise that will facilitate the design and execution of clinical trials, so that new information is gained, and that will ultimately inform care1 . In this commentary, we explore these problems and suggest an alternative approach to the development of clinical guidance in areas where evidence is lacking.